2013
DOI: 10.1016/j.juro.2013.05.021
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Endorectal 3 Tesla Multiparametric Magnetic Resonance Imaging for Extraprostatic Extension in Patients with Low, Intermediate and High Risk Prostate Cancer

Abstract: For adequate patient counseling, knowledge of predictive values of multiparametric magnetic resonance imaging for extraprostatic extension is of utmost importance. High negative predictive value, important for decisions on nerve sparing strategies at radical prostatectomy, is only reached in low risk subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 29 publications
8
97
0
7
Order By: Relevance
“…[4,5,[9][10][11] In our study, the specificity, sensitivity, and positive and negative predictive values of ECE were 95%, 25%, 66%, and 77%, respectively. We evaluated the patients who had RARP with or without preoperative MRIguided dissection planning.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…[4,5,[9][10][11] In our study, the specificity, sensitivity, and positive and negative predictive values of ECE were 95%, 25%, 66%, and 77%, respectively. We evaluated the patients who had RARP with or without preoperative MRIguided dissection planning.…”
Section: Discussionsupporting
confidence: 47%
“…[5][6][7][8][9] It is estimated that mp-MRI detects ECE with 48-76% accuracy. [4,[10][11][12][13][14] Walz et al [15] detailed the anatomy of the prostate and adjacent tissues, especially the fascia and NVB. In light of these studies, preoperative mp-MRI of the prostate may guide surgeons' dissection plans for RARP.…”
Section: Introductionmentioning
confidence: 99%
“…There were 20/21 (95.2%) studies that consistently demonstrated upstaging by MRI, 33,36 and upstaging by MRI compared to routine clinical staging. 12,13,16,17,20,21,23,30,32,34,[37][38][39][40][41][42][43][44][45] Upstaging by MRI was correct by pathology in seven studies, with a range from 11-85%. 16 …”
Section: Key Evidencementioning
confidence: 97%
“…There were 19/49 (38.8%) primary studies of MRI ≥1.5 T + ER ± DWI, DCE, MRS that considered the detection of EPE and/or SVI [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (Figs. 2, 3).…”
Section: Key Evidencementioning
confidence: 99%
“…SVI is also relatively common, with recent large surgical series reporting rates of 4.5% to 12.7%. [4][5][6] For all of these reasons, early knowledge of SVI is critical for appropriate patient counseling, treatment selection, and planning.…”
Section: Introductionmentioning
confidence: 99%